2022
DOI: 10.3168/jds.2021-20951
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions of dairy farmers regarding antibiotic use: Lessons from a developing country

Abstract: In lower-and middle-income countries, uncontrolled use of antibiotics is causing antimicrobial resistance, affecting both animal welfare and public health. Meanwhile, studies on antibiotic use in these countries are limited. A crucial step to limit the spread of antimicrobial resistance (AMR) is to examine the use of these drugs and identify its determinants. The aim of our study, the first of its kind in Lebanon, was to assess dairy farmers' knowledge and awareness of antimicrobial use (AMU) and AMR. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
2
16
2
2
Order By: Relevance
“…antibiotics are used without having been prescribed. This problem could be reduced by educational campaigns for the public and setting up and controlling policies and regulations regarding antibiotic sales [37,39,44]. In addition, involving all pharmacists to educate all patients every time during dispensing antibiotics would be important.…”
Section: Plos Onementioning
confidence: 99%
“…antibiotics are used without having been prescribed. This problem could be reduced by educational campaigns for the public and setting up and controlling policies and regulations regarding antibiotic sales [37,39,44]. In addition, involving all pharmacists to educate all patients every time during dispensing antibiotics would be important.…”
Section: Plos Onementioning
confidence: 99%
“…Significantly, underdosing was reported by many scientists as being the main reason for dangerously developing ABR. In addition, pathogens exposed to subinhibitory concentrations of the antibiotics will lead to more survival of bacterial populations in that animal, generating an advanced resistance to the antibiotics [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Veterinarians and farmers have critical roles for use of antimicrobials in dairy farms. Many studies have investigated farmers' knowledge, attitudes, awareness, behaviors and practices relating to the antibiotic use and antibiotic resistance in dairy farms in the different countries worldwide, such as France (Dernburg et al, 2007), Peru (Redding et al, 2014), the Netherlands (Speksnijder et al, 2017), Denmark (Oliveira et al, 2018), Lebanon (Dankar et al, 2022). These studies indicated that farmers' knowledge, attitudes, awareness can significantly influence their behaviors and practices to antibiotic use for animals.…”
Section: Introductionmentioning
confidence: 99%